Caracterización del medio físico para determinar áreas de protección hídrica en la microcuenca del río Guano. - Amaya Lema, Jonathan Naun (2025)
The thesis titled "Characterization of the Physical Environment to Determine Water Protection Areas in the Guano River Micro-watershed" addresses the need to identify priority areas for water conservation in this strategic region of Chimborazo Province, Ecuador. The main objective was to characterize the micro watershed geomorphologically and hydrologically, analyze changes in land use and vegetation cover over time, and delineate key water protection areas. A methodology based on Geographic Information Systems (GIS), satellite imagery, and hydrological modeling using HEC-HMS was employed to analyze hydrological dynamics in three periods: 2000-2010, 2015-2019, and 2020-2024. The research identified a significant loss of vegetation cover in the upper parts of the micro-watershed, accompanied by an increase in agricultural areas in the middle and lower zones, which has elevated erosion risks and negatively impacted water regulation capacity. The main results highlighted critical zones for aquifer recharge and areas highly vulnerable to degradation, enabling the delimitation and classification of priority water protection areas. These areas were found to play an essential role in biodiversity conservation, hydrological cycle regulation, and water supply. The findings provide a foundation for integrated water management strategies, contributing to the sustainability of resources in the Guano River micro-watershed.